Event design handbook : systematically design innovative events using the event canvas - Frissen, Roel, ....-; Janssen, Ruud, ....-; Luijer, Dennis, ....- (Amsterdam : BIS Publishers, 2020)
Some of the most life-changing connections are made at events. But if you can't design events, how can you change your world ? The answer? This handbook will change the way you think about how events change the world you live in. It shows the way to re-design your world on one sheet of paper using the Event Canvas.This book identifies the starting point of any event and outlines steps of how events come to life. It focuses on the DNA of specific aspects of events, and provides insight into how to observe and analyze events, understand stakeholders, and define behavioural changes required to deliver value. It also identifies the levers and mechanisms that influence such behavioural changes in event design.This handbook lays the foundation for creating a common language. A language that can be spoken and understood by those who know and those who don't yet know the mechanics of events. It is a pragmatic approach for designing and creating events that matter.
Keywords: Event management